Task-based approach: for and against; Лингвистические и культурологические аспекты современного инженерного образования - Буран А. Л. Анна Леонидовна (2024, 2024)
This paper deals with the problem how to motivate students to learn the English language. We refer to task-based approach. We focus on different types of tasks that help students improve their knowledge of English through communication and collaboration with others. We observe how to plan the lesson using six types of tasks to improve speaking skills, get a foreign language fluency in an easy and an exciting way